Dietary flaxseed lignan extract lowers plasma cholesterol and glucose concentrations in hypercholesterolaemic subjects - Zhang, Wei; Wang, Xiaobing; Liu, Yi; Tian, Haimei; Flickinger, Brent; Empie, Mark W.; Sun, Sam Z. (British journal of nutrition, 2008)
Lignans, derived from flaxseed, are phyto-oestrogens being increasingly studied for their health benefits. An 8-week, randomised, double-blind, placebo-controlled study was conducted in fifty-five hypercholesterolaemic subjects, using treatments of 0 (placebo), 300 or 600 mg/d of dietary secoisolariciresinol diglucoside (SDG) from flaxseed extract to determine the effect on plasma lipids and fasting glucose levels. Significant treatment effects were achieved (P < 0·05 to < 0·001) for the decrease of total cholesterol (TC), LDL-cholesterol (LDL-C) and glucose concentrations, as well as their percentage decrease from baseline. At weeks 6 and 8 in the 600 mg SDG group, the decreases of TC and LDL-C concentrations were in the range from 22·0 to 24·38 % respectively (all P < 0·005 compared with placebo). For the 300 mg SDG group, only significant differences from baseline were observed for decreases of TC and LDL-C. A substantial effect on lowering concentrations of fasting plasma glucose was also noted in the 600 mg SDG group at weeks 6 and 8, especially in the subjects with baseline glucose concentrations ≥ 5·83 mmol/l (lowered 25·56 and 24·96 %; P = 0·015 and P = 0·012 compared with placebo, respectively). Plasma concentrations of secoisolariciresinol (SECO), enterodiol (ED) and enterolactone were all significantly raised in the groups supplemented with flaxseed lignan. The observed cholesterol-lowering values were correlated with the concentrations of plasma SECO and ED (r 0·128–0·302; P < 0·05 to < 0·001). In conclusion, dietary flaxseed lignan extract decreased plasma cholesterol and glucose concentrations in a dose-dependent manner.